Application of dynamic electricity: Series and Parallel learning model with ISLE-based STEM approach for students with disabilities - Yuli Andriani; Irwandi Irwandi; Mursal Mursal; Mailizar Mailizar; Elin Yusibani (PSI-Aceh, 2021)
Abstrak. STEM Research Center telah mengembangkan beberapa modul dengan pendekatan model STEM berbasis Investigative Science Learning Environment (ISLE) dan telah berhasil mengimplementasikan pada sekolah umum di Aceh. Modul yang telah dikembangkan selanjutnya akan diterapkan kepada siswa penyandang disabilitas tunarungu di SMALB YPAC Kota Banda Aceh. Penerapan model pembelajaran menggunakan STEM berbasis ISLE yakni didasarkan pada kegiatan observasi dan diskusi berkaitan dengan empat bidang disiplin ilmu yakni sains, teknologi, enjinering dan matematika. Modul pembelajaran yang dikembangkan terdapat dua kegiatan belajar, yaitu kegiatan belajar yang berkaitan dengan eksperimen pengamatan dan kegiatan belajar yang berkaitan kegiatan eksperimen sederhana dengan menguji kebenaran hasil prediksi. Rangkaian listrik dinamis yang diberikan adalah rangkaian sederhana yang dipasangkan secara seri dan paralel. Untuk alat peraga listrik dinamis yang digunakan, pengamatan tidak mengalami permasalahan. Siswa dapat mengikuti lembar kerja modul ISLE dengan baik. Proses diskusi dalam kelompok masih dapat dilakukan, namun terdapat masalah dalam hal mengkomunikasikan ide-ide antar kelompok.Abstract. STEM Research Center has developed several modules with the ISLE-based STEM model approach and has successfully implemented them in regular schools in Aceh. The module that has been developed will then be applied to students with hearing disabilities at YPAC High School Banda Aceh City. The application of the learning model uses the ISLE-based STEM which is based on observation and discussion activities related to four fields, namely science, technology, engineering, and mathematics. The learning module developed has two learning activities, namely learning activities related to experimental observations and learning activities related to simple experimental activities by testing the correctness of the predicted results. A given dynamic electric circuit is a simple circuit that is paired in series and parallel. For dynamic electric props used, the observation does not experience any problems. Students can follow the ISLE module worksheets well. The discussion process in groups is still possible, but there are problems in communicating ideas between groups.Keywords: ISLE based STEM module, Deaf, Dynamic electricity